Modern features of the cryptocurrency use for terrorist financing, money laundering and other unlawful activities: prospective countermeasures (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The author provides an assessment of the current threats and risks associated with the use of cryptocurrencies for illegal purposes, taking into account the conclusions of international institutions. The modern methods (mechanisms) of using cryptocurrencies as a means of payment in the drug trade, for legalisation of proceeds of crime, financing of terrorist, intelligence and subversive, separatist and other illegal activities in Ukraine, including under martial law, are highlighted. The purpose of the article is to clarify the peculiarities of the cryptocurrency use in illegal activities in the current conditions in order to develop proposals for improving the counteraction to the illegal use of cryptocurrencies. The novelty of the study is that it analyses the peculiarities of such use of cryptocurrencies in the context of Russia’s full-scale military aggression against Ukraine, which remain poorly understood by scholars.Given the peculiarities of illegal use of cryptocurrencies in Ukraine, the author identifies the need to improve the work of authorized state bodies to counteract their use for illegal purposes, which is especially relevant in the context of incomplete legal definition of their status, imperfect state policy in the field of regulation of cryptocurrency circulation and martial law. Promising measures to counteract the use of cryptocurrencies in illegal activities are outlined, and ways to improve them are suggested. The author identifies the need to complete the process of legislative definition of the status and regulation of cryptocurrency circulation; to improve the national system of countermeasures, to establish coordination of the work of authorised state bodies; to ensure the implementation of international standards; to establish public-private partnership and cooperation between competent entities of Ukraine and foreign countries.